2019
DOI: 10.1111/cid.12817
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue augmentation applying a collagenated porcine dermal matrix during second stage surgery: A prospective multicenter case series

Abstract: Background The achievement and preservation of an adequate amount of soft tissue around implants is a critical factor for the prognosis of the treatment. Purpose To evaluate the effectiveness of a porcine dermal matrix applied during second stage implant surgery for horizontal soft tissue augmentation and preservation of dimensional stability. Materials and Methods Twenty patients (mean age 50.2 ± 11.9 [SD] years) candidate to implant therapy and requiring soft tissue augmentation were recruited in four center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 30 publications
(79 reference statements)
1
22
0
Order By: Relevance
“…The mean increase in buccal soft tissue thickness in these studies ranged from 0.70 mm to 1.16 mm after 3 to 12 months of follow-up. One prospective study was found on OsteoBiol Derma Standard ® (Tecnoss, Giaveno, Italy) using the same volumetric measurement method as described in the present study [47]. An initial tissue gain of 1.57 mm was seen two weeks post-augmentation.…”
Section: Discussionmentioning
confidence: 68%
“…The mean increase in buccal soft tissue thickness in these studies ranged from 0.70 mm to 1.16 mm after 3 to 12 months of follow-up. One prospective study was found on OsteoBiol Derma Standard ® (Tecnoss, Giaveno, Italy) using the same volumetric measurement method as described in the present study [47]. An initial tissue gain of 1.57 mm was seen two weeks post-augmentation.…”
Section: Discussionmentioning
confidence: 68%
“…The scaffold resorbs upon transplantation, leaving the ECM and functional fibroblasts which secrete appropriate growth factors, allowing faster healing of the tissue [237]. (B) Natural polymers and scaffolds Human-derived Acellular Dermal Matrices (ADM) are one of the more common scaffold materials which mimic ECM to provide a favourable environment for cell growth and growth factor exchange [238]. Similar scaffolds can be generated of xenogeneic origin like porcine graft, which showed positive outcomes as a scaffold [239].…”
Section: Mucosal Graftsmentioning
confidence: 99%
“…However, their stiffness and fragility were seen to increase because they have been recently used mixed with non-resorbable polymers, (MMA)1-co-(HEMA)1 and (MA)3co-(HEA)2. As the synthetic grafts have limited biological interactions, they have to be impregnated (B) Natural polymers and scaffolds Human-derived Acellular Dermal Matrices (ADM) are one of the more common scaffold materials which mimic ECM to provide a favourable environment for cell growth and growth factor exchange [238]. Similar scaffolds can be generated of xenogeneic origin like porcine graft, which showed positive outcomes as a scaffold [239].…”
Section: Mucosal Graftsmentioning
confidence: 99%
“…It is therefore clinically recommended a keratinized mucosa width of 2 mm, which is the same size that it is suggested for an adequate keratinized gingiva zone around the teeth [ 5 ]. When the mucosa thickness is higher than 2 mm, the human eye is no longer able to detect light reflection (translucency) differences of zirconia or titanium abutments underneath the soft tissue [ 6 ].…”
Section: Introduction To Soft Tissue Augmentation Background Of Tmentioning
confidence: 99%
“…Buccal fat pad and free buccal mucosa grafts have also been proposed [ 1 ]. Thereby, an alternative treatment for the autogenous soft tissue graft is recommended based on the good clinical integration of collagen-based dermal matrices in implant and plastic periodontal surgery [ 6 ].…”
Section: Introduction To Soft Tissue Augmentation Background Of Tmentioning
confidence: 99%